CHECKERBOARD ASSAY TO ASSESS SYNERGISTIC ACTION OF FLUCONAZOLE AND ESSENTIAL OILS OF AJWAIN AND CORIANDER AGAINST CANDIDA SPP. - YOOSUF, S,; KAMAT, S.D.,; KAMAT, D. V., (International Journal of Pharma and Bio Sciences, 2016)
Candida a commensal fungus, represents one of the major causes of mucosal and systemic infection. They show remarkable resistance to various first-line and second-line antifungal medications, namely, Fluconazole and Echinocandins. Checkerboard Assay was used to establish synergistic action of Fluconazole and essential oil of Coriandrum sativum and Fluconazole and essential oil of Trachyspermum ammi against Candida spp. The ∑FIC value obtained by Checkerboard Assay was 0.375 and 0.5 for Candida spp. tested in combination for essential oils of Ajwain and Coriander oil. Thus, indicating synergistic interaction between Fluconazole and the tested essential oils. The active components present in the essential can be used in combination with the antifungal under study. There is a need for in-vivo studies in order to assess the safety of the combination, though.